The impact of the internet on trade in education - Tay, Christina (Technological and Economic Development of Economy, 2015)
The purpose of this study is to investigate how the Internet impacts trade in education. Divided into three time frames – 2000 to 2006, 2007 to 2012 and 2000 to 2012, data on 189 countries was used to compare the impact of different intensities of the Internet access on trade in education. This research uses the following methods to analyse data: pooled ordinary least squares regression, fixed-effects model and random effects model. Results suggest that the Internet facilitates trade in education, the impact of which is between 16.4% and 21% for every 0.01% increase in Internet access. Larger countries and countries that share a common language show a highly significant impact of the Internet on trade in education for all three time frames at 0.01%. However, economic health of a country does not necessarily imply greater trade. This study finds mixed results for fixed (wired) broadband over the three time frames. The results explain between 63.2% and 74.9% of the impact of the Internet on trade in education. Finally, the results of this study strongly suggest that improving Internet access in a country will stimulate trade in education.